2019
DOI: 10.1093/toxsci/kfz244
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury Induces Metabolic Alterations in Caenorhabditis elegans: Role for C/EBP Transcription Factor

Abstract: Methylmercury (MeHg) is a well-known neurotoxicant; however, its role in metabolic diseases has been gaining wider attention. We have previously shown that MeHg causes metabolic alterations in Caenorhabditis elegans, leading to decreased nicotinamide adenine dinucleotide cofactor, mitochondrial dysfunction, and oxidative stress. We were, therefore, interested in whether MeHg also affects nutrient metabolism, particularly lipid homeostasis, which may contribute to the development of metabolic conditions such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 81 publications
2
22
0
Order By: Relevance
“…Certain inconsistencies between the adipotropic effects of Hg reported in these two studies may be explained by the difference in the dose of metal exposure; higher dose 22 results in adipogenic response inhibition due to the potential toxic (including pro-oxidant) effects. In addition to the studies in mice demonstrating a significant impact of Hg exposure on PPARγ, our recent findings from a Caenorhabditis elegans model revealed a significant impact of 10 to 20 µM MeHg on lipid metabolism regulatory genes, including pro-adipogenic worm orthologs to human SREBP and C/EBPs 23 , due to MeHg being another regulator of adipogenesis. In contrast to the previously mentioned studies, one study demonstrated that in C57BL/6J mice orally exposed to 0.5 or 5 ppm MeHg (concentrations that failed to induce adipogenic gene expression in visceral adipose tissue), a reduction of adipose tissue cumulation was associated with MeHg-induced increase in hypothalamic pro-opiomelanocortin (POMC) expression 24 .…”
Section: Adipotropic Effects Of Heavy Metalsmentioning
confidence: 78%
“…Certain inconsistencies between the adipotropic effects of Hg reported in these two studies may be explained by the difference in the dose of metal exposure; higher dose 22 results in adipogenic response inhibition due to the potential toxic (including pro-oxidant) effects. In addition to the studies in mice demonstrating a significant impact of Hg exposure on PPARγ, our recent findings from a Caenorhabditis elegans model revealed a significant impact of 10 to 20 µM MeHg on lipid metabolism regulatory genes, including pro-adipogenic worm orthologs to human SREBP and C/EBPs 23 , due to MeHg being another regulator of adipogenesis. In contrast to the previously mentioned studies, one study demonstrated that in C57BL/6J mice orally exposed to 0.5 or 5 ppm MeHg (concentrations that failed to induce adipogenic gene expression in visceral adipose tissue), a reduction of adipose tissue cumulation was associated with MeHg-induced increase in hypothalamic pro-opiomelanocortin (POMC) expression 24 .…”
Section: Adipotropic Effects Of Heavy Metalsmentioning
confidence: 78%
“…Previously, we have shown that fat storage sites are increased by MeHg through two methods, BODIPY 493/503 and Nile Red [10]. As the Nile Red method amends itself to screening multiple treatment groups, we chose to quantify fat storage sites using this method.…”
Section: Nile Red Stainingmentioning
confidence: 99%
“…We have previously shown that MeHg increases the triglyceride content of N2 worms fed OP50 [10]. As HB101, HT115, and 2x cholesterol OP50 contained different lipid profiles to OP50, we were interested in whether the worms would accumulate lipids in response to MeHg at similar levels.…”
Section: Bacterial Diet Altered Lipid Accumulation In Response To Mehgmentioning
confidence: 99%
See 2 more Smart Citations